Depressive disorder among postpartum women: an analysis according to self-reported race/color. - Lima, Rosa Vanessa Alves; Melo, Luciana Camargo de Oliveira; Barbosa, Nayara Gonçalves; Arciprete, Ana Paula Rodrigues; Monteiro, Juliana Cristina dos Santos (Acta Paulista de Enfermagem, 2023)
Objective: To identify the race/color self-reported by women 60 days postpartum; to identify the prevalence of signs of depressive disorder among these women and to verify the association between signs of depressive disorder and the self-reported race/color. Methods: Cross-sectional study carried out in a noncapital city in the state of São Paulo. An instrument with sociodemographic data and the Edinburgh Postnatal Depression Scale were used for data collection. Data was analyzed using the Statistical Package for Social Sciences, SPSS, version 17.0. Results: A total of 186 women participated in this study, 60.8% reported being brown, 24.2% had signs of depressive disorder and, among these, 81.7% were black. Signs of depressive disorder were associated with the variables: number of children (p=0.006), planned pregnancy (p=0.04) and type of delivery (p < 0.001). Conclusion: The results of this study contribute to greater visibility of the issue of women's mental health, specifically of black women, because even though no significant association was identified among those who showed signs of depressive disorder, most were black.